Pemilihan Nazhir Dalam Optimalisasi Pengelolaan Wakaf Uang - Wulandari, Shinta; Effendi, Jaenal; Saptono, Imam Teguh (Jurnal Aplikasi Bisnis dan Manajemen, 2019)
There is a gap between the potency and real data of cash waqf raising in Indonesia. Hence, an effective strategy is needed to develop the potential of cash waqf. This research aimed to analyze whether the Islamic Bank can be an alternative to the institutional development of cash waqf in Indonesia (Nazhir) and analyze the strategies needed to optimize the cash waqf management. This research used descriptive quantitative and qualitative approaches based on literature studies, observation, and questionnaires by using an analytical network process (ANP) method. The alternative selection of cash waqf management strategy through competent and professional Nazhir is determined by five criteria; including Accountability, Product, Human Resources, Regulation, and Network. In Nazhir selection’s analysis in optimizing cash waqf management, these five criteria have an important role in accordance with their respective functions to produce management strategies and cash waqf development through competent and professional Nazhir. The results showed that Islamic Banking is the most recommended Nazhir in determining the potential strategy of cash waqf development with the highest weighted score. Accountability is the most influential criterion in determining the cash waqf development strategy with professionalism in management as the most influential sub-criteria.Keywords: ANP, cash waqf, islamic banking, nazhirAbstrak: Saat ini diperlukan strategi yang efektif untuk mengembangkan potensi wakaf uang, mengingat potensi yang sangat besar namun realisasi penghimpunan masih belum optimal. Tujuan penelitian ini untuk menganalisis apakah Bank Syariah dapat menjadi alternatif pengembangan kelembagaan wakaf uang di tanah air (nazhir wakaf uang), dan menganalisis strategi yang diperlukan dalam mengoptimalkan pengelolaan wakaf uang. Penelitian menggunakan pendekatan deskriptif kuantitatif dan kualitatif berdasarkan studi literatur, observasi, dan kuesioner dengan menggunakan analytical network process (ANP).Alternatif pemilihan strategi pengelolaan wakaf uang melalui Nazhir yang kompeten dan professional ditentukan oleh lima kriteria meliputi Akuntabilitas, Produk, SDM, Regulasi, dan Jangkauan. Dalam analisis pemilihan nazhir dalam optimalisasi pengelolaan wakaf uang, kelima kriteria tersebut memiliki peranan penting sesuai dengan fungsinya masing-masing untuk dapat menghasilkan strategi pengelolaan dan pengembangan wakaf uang melalui Nazhir yang kompeten dan profesional. Hasil penelitian menunjukan bahwa Perbankan Syariah adalah Nazhir yang paling direkomendasikan dalam penentuan strategi potensi pengembangan wakaf uang dengan nilai bobot tertinggi. Akuntabilitas adalah kriteria yang paling berpengaruh dalam menentukan strategi pengembangan wakaf uang dengan profesionalisme pengelolaan sebagai subkriteria yang paling berpengaruh. Kata kunci: ANP, wakaf uang, perbankan syariah, nazhir